Dismenore dan Disrupsi Akademik: Analisis Dampak Nyeri Menstruasi terhadap Regulasi Emosi dan Produktivitas Mahasiswi - Syifa Dwi Ariyanti; Septi Gumiandari (Kampus Akademik Publiser, 2026)
Menstrual pain (dysmenorrhea) is a health problem frequently experienced by female university students, and this issue not only affects their physical condition but can also impact their emotional state and academic activities. Untreated menstrual pain has the potential to disrupt learning concentration, task completion, and emotional stability, thereby affecting academic productivity. This study aims to: (1) analyze the impact of menstrual pain (dysmenorrhea) on emotional regulation among female students, (2) identify the impact of dysmenorrhea on academic productivity (such as concentration, attendance, and task completion), (3) examine the relationship between emotional regulation and academic productivity in female students experiencing dysmenorrhea, and (4) describe the severity of dysmenorrhea experienced by female students and its association with academic activity interference. This research employed a quantitative approach with a cross-sectional design, and 31 female students experiencing dysmenorrhea participated as respondents through purposive sampling technique. Data were collected using an online questionnaire covering dysmenorrhea severity, emotional regulation, and academic productivity. Data were analyzed descriptively using frequency distributions and percentages to describe respondent characteristics and the tendency of relationships between variables. The results showed that: (1) many female students had difficulty controlling their emotions (64.5%) and exhibited emotional instability (58.1%), (2) dysmenorrhea also affected decreased learning concentration (54.8%), delayed task completion (67.7%), and disrupted lecture attendance (25.8%), (3) as many as 58.1% of respondents stated that the ability to manage emotions helped them remain productive while experiencing dysmenorrhea, and (4) the majority of respondents experienced moderate (48.4%) to severe (35.5%) dysmenorrhea, with greater concentration and emotional disturbances at higher pain levels. Dysmenorrhea is associated with impaired emotional regulation and decreased academic productivity among female students, where the higher the severity of dysmenorrhea, the greater the perceived disturbance in emotional aspects and academic activities. These findings highlight the importance of reproductive health education and emotional management strategies to support female students' academic success.